Mitochondrial Dysfunction in the Liver and Antiphospholipid Antibody Production Precede Disease Onset and Respond to Rapamycin in Lupus‐Prone Mice. Issue 11 (27th October 2016) - Oaks, Zachary; Winans, Thomas; Caza, Tiffany; Fernandez, David; Liu, Yuxin; Landas, Steve K.; Banki, Katalin; Perl, Andras
Abstract : Objective: Antiphospholipid antibodies (aPL) constitute a diagnostic criterion of systemic lupus erythematosus (SLE), and aPL have been functionally linked to liver disease in patients with SLE. Since the mechanistic target of rapamycin (mTOR) is a regulator of oxidative stress, a pathophysiologic process that contributes to the development of aPL, this study was undertaken in a mouse model of SLE to examine the involvement of liver mitochondria in lupus pathogenesis. Methods: Mitochondria were isolated from lupus‐prone MRL/lpr, C57BL/6.lpr, and MRL mice, age‐matched autoimmunity‐resistant C57BL/6 mice as negative controls, and transaldolase‐deficient mice, a strain that exhibits oxidative stress in the liver. Electron transport chain (ETC) activity was assessed using measurements of oxygen consumption. ETC proteins, which are regulators of mitochondrial homeostasis, and the mTOR complexes mTORC1 and mTORC2 were examined by Western blotting. Anticardiolipin (aCL) and anti–β2 ‐glycoprotein I (anti‐β2 GPI) autoantibodies were measured by enzyme‐linked immunosorbent assay in mice treated with rapamycin or mice treated with a solvent control. Results: Mitochondrial oxygen consumption was increased in the livers of 4‐week‐old, disease‐free MRL/lpr mice relative to age‐matched controls. Levels of the mitophagy initiator dynamin‐related protein 1 (Drp1) were depleted while the activity of mTORC1 was increased in MRL/lpr mice. In turn, mTORC2 activity was decreased in MRL and MRL/lpr mice. In addition, levels of aCL and anti‐β2 GPI were elevated preceding the development of nephritis in 4‐week‐old MRL, C57BL/6.lpr, and MRL/lpr mice. Transaldolase‐deficient mice showed increased oxygen consumption, depletion of Drp1, activation of mTORC1, and elevated expression of NADH:ubiquinone oxidoreductase core subunit S3 (NDUFS3), a pro‐oxidant subunit of ETC complex I, as well as increased production of aCL and anti‐β2 GPI autoantibodies. Treatment with rapamycin selectively blocked mTORC1 activation, NDUFS3 expression, and aPL production both in transaldolase‐deficient mice and in lupus‐prone mice. Conclusion: In lupus‐prone mice, mTORC1‐dependent mitochondrial dysfunction contributes to the generation of aPL, suggesting that such mechanisms may represent a treatment target in patients with SLE.